Hourly estimate of total extraterrestrial solar irradiance - Plasencia, Edson (2007)
Total Extraterrestrial Solar Irradiance (TSI) is the amount of energy from the sun, per unit area, received by every point above the Earth's atmosphere, at each instant of time; therefore, it is a quantity that varies both spatially and temporally, according to the position of a particular point on Earth and its position with respect to the Sun. A series of methodological proposals are currently available to estimate TSI on a daily basis, however, there are places such as Antarctica, where the synoptic variability is very high, therefore, it is necessary to adapt or develop a methodology that allows an energy balance to be carried out on a shorter time scale. Henceforth, the adaptability at the hourly level of the most important models proposed at the daily level will be analyzed and, finally, a methodology will be proposed to be used in studies of high spatial and temporal resolution, such as Antarctic studies at the hourly level.